An Inflow of Foreign Aid in Nepal - Karna, Sohan Kumar (Economic Journal of Nepal, 2011)
Foreign aid is a much debated and controversial phenomenon. The debate is mainly centered on whose interest aid actually serves—the recipients’ or donors’. Intellectuals, thinkers. development practitioners and writers have experienced difficulty on the rationale, adequacy, efficiency and effectiveness of aid. Traditionally, foreign aid sus supposed to overcome the savingsinvestment gap. Hard currency and technological shortages in recipient countries, which would ultimately uplift the developing economy and living standards of people. As understandings of development changed from being not so much a materialistic pursuit but a humanitarian one, the rationale for aid likewise shifted from being needed to fulfill hard economic aggregates to contributing to human development through poverty reduction for socioeconomic. Political and cultural enhancement. Increased aid over the years has helped reduce poverty and create a just and equal world. Key words: Foreign aid; Economic development; Poverty reduction Economic Journal of Nepal A Quarterly Publication of the Central Department of Economics, Tribhuvan University, Kirtipur, Kathmandu Vol. 30, No.4, October-December, Issue No. 120, 2007 Page: 201-214 Uploaded date: 22 July, 2011